The Role of Technology in Digital Financial Services Transformation - Syafiq; Grace Tan Mei Ling (Outline Publisher, 2024)
The digital transformation of financial services, driven by technological advancements, is reshaping the global financial landscape. Technologies such as mobile payments, blockchain, artificial intelligence (AI), cloud computing, and machine learning have not only increased efficiency and accessibility but have also expanded financial inclusion, enabling millions to access banking services previously unavailable to them. Mobile money platforms like M-Pesa in Kenya and Alipay in China exemplify the potential of digital financial services in bridging the gap between the banked and unbanked populations. Additionally, blockchain technology has enabled innovations like decentralized finance (DeFi), cryptocurrencies, and smart contracts, which are reducing costs and enhancing transparency in financial transactions. AI and machine learning are improving risk management, fraud detection, and customer personalization. However, the rapid expansion of digital financial services also introduces challenges related to cybersecurity, privacy, regulatory compliance, and the digital divide. Ensuring the security of digital platforms and creating inclusive access for underserved populations are key areas requiring attention. Ultimately, while technology has brought significant opportunities, it is essential to address these challenges through effective regulation and investment in infrastructure to ensure that digital financial services contribute to global financial empowerment and economic growth.